Технологічна трансформація металургійного комплексу України: перехід до гнучких систем напівбезперервного циклу та безкоксової металургії - Рябий, Д.В.; Шарандін, К.М.; Пісмарьов, К.Є. (Physico-technological Institute of Metals and Alloys, 2026)
The article is devoted to a comprehensive analysis of the transformation of Ukraine’s metallurgical industry under conditions of a forced shift in the production paradigm. The paper substantiates the necessity of structural and technological transformation of Ukraine’s metallurgical complex in the context of wartime losses of production capacities, disruption of raw material supply chains, and energy constraints. It analyzes the macroeconomic role of metallurgy prior to 2022 and the scale of the industry’s degradation resulting from the destruction of key assets of the blast furnace cycle and the coke-chemical base. It is proven that the restoration of the traditional coke-blast furnace model is technically and economically impractical, and that the strategic alternative should be a transition to coke-free metallurgy based on direct reduced iron (DRI) technologies – Midrex and Corex – in combination with electric arc furnaces (EAF). A model of a decentralized network of mini- and midi-mills focused on flexible steel production to meet the needs of the defense industry and post-war reconstruction is proposed. Particular attention is paid to the application of semi-continuous steel casting as a technology that ensures adaptability to an intermittent energy supply regime, high metal quality, and reduced production losses. It is substantiated that the proposed transformation can enhance the technological resilience of the industry, reduce import dependence, and integrate Ukrainian metallurgy into global value chains. Additional emphasis is placed on the need to form a new investment development model that involves attracting international financing, implementing public-private partnership mechanisms, and applying green transition instruments within the framework of European climate policy. The key risks of implementing the new industry architecture are identified, and the institutional prerequisites for its phased implementation during wartime and post-war periods are outlined.